Sol-gel synthesis of silver/titanium dioxide (Ag/TiO2) core-shell nanowires for photocatalytic applications - Chin, Suk Fun; Pang, Suh Cem; Freda Emmanuel, Idely Dom (Elsevier, 2011)
Silver/titanium dioxide (Ag/TiO2) core-shell nanowires were synthesized by direct coating of TiO2 shells on the surface of silver nanowires (AgNWs) through a simple sol-gel process. TEM image and EDX elemental analysis had confirmed the presence of TiO2 coating on the surface of AgNWs. The thickness of titanium dioxide coating was about 10 nm. These Ag/TiO2 core-shell nanowires showed good photocatalytic activities in the decomposition of methylene blue as a model organic dye in aqueous solution under UV light irradiation. Ag/TiO2 core-shell nanowires are potentially useful in photocatalytic applications.